Influence of supplemental fat and monensin plus tylosin on performance and carcass traits of finishing steers - Brandt, Robert T., Jr.; Elliott, J.K.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Interactions between supplemental fat (3.5%) and monensin plus tylosin (25 plus 10 g/ton, respectively) on animal performance and carcass traits were evaluated in a 125-d finishing trial. Interactions on feed consumption (P=.07) and feed efficiency (P=.11) suggested that the ionophore response was diminished in the presence of supplemental fat. Steers fed monensin plus tylosin had a lower (P=.005) incidence of liver abscesses whether fat was fed or not, indicating that supplemental fat had no effect on tylosin activity.
Keywords: Beef; Monensin; Tylosin; Fat; Liver abscess; Cattle performance